Aplicação do índice de mobilidade urbana sustentável (imus) em Goiânia. - Abdala, Ivanilde Maria de Rezende (2013)
The increasing concentration of the population in the cities resulted from a very rapid and uncontrolled urbanization process and the absence of public policies to regulate the indiscriminate use of private motorized vehicles has resulted, in the major Brazilian cities, in a significant increase of the number of vehicles and, hence in the deterioration of quality of urban life. The necessity of an urban planning that is able to better integrate the use and occupation of urban spaces and the mobility derived from them, has lead to many studies and research in order to develop indicators and indexes to measure the quality of life associated with the quality of mobility. Intending to do that Costa, 2008, developed the Index of Sustainable Urban Mobility (I_SUM). This index evaluates qualitatively and qualitatively many aspects belonging to the concept of mobility, including the essential scenarios social, economic and environmental. This study aims the applications of the index in Goiania (GO) city, in order to make a diagnosis of the urban mobility conditions in the city in the light of this methodology and offer subsidies to the city decision- makers referring to implementation and monitoring of public policies to promote the sustainable urban mobility and hence the quality of urban life. Results of the study indicate that the city it is still far from to reach a high level of sustainable mobility (1,0), but despite of its not very satisfactory index (0,658), the value indicates that the city it is in the track towards the principles of sustainable urban mobility.